Evaluation of information and communication technology sector in the teaching process and strategic collaboration between universities and industry. Issue 3 (27th February 2019) - Cvetković, Biljana Novković; Gligorijević, Milan; Petković, Dalibor; Jović, Srđan; Milovančević, Miloš; Nikolić, Vlastimir
Abstract: The main purpose of the study was to evaluate the information and communication technology (ICT) sector in the teaching process based on teachers' attitudes and the strategic collaboration between universities and industry. The most common issue faced by the graduated students is to find a desired job at the end of the course of study. The main obstacle in finding a desired job is not enough ICT knowledge, which is not adequately learned at universities. On the other hand, the ICT teaching process at universities could be slow because many teachers do not have the right attitude toward ICT application in the learning process. In this study, a survey was performed among ICT working students and ICT teachers as well to reveal the relationship between the skills required for a job and the skills being taught at universities; whether the employability skills of fresh graduates increase hiring opportunities. The sample of examinees for this study consisted of the ICT sector in the European Union as well as ICT teachers based on the World Bank database. The proposed model was analyzed using structural equation modeling. It was found that the relationship between the academic program and job market along with ICT skills affected the employability factor. Hence the relationship between the academic program and job market significantly affects the employability factor. In effect, more focus on designing the academic curriculum is needed.